HUBUNGAN TINGKAT KECEMASAN DENGAN RISIKO TERJADINYA CEDERA OLAHRAGA PADA PEMAIN SEPAKBOLA AMATIR - Ramadhan Fiqri Maulana, (2023)
Abstract Background: There is a relationship between anxiety level and the risk of sports injury in teenage amateur soccer players and is considered very interesting to know the anxiety caused by these injuries. Various previous studies have examined aspects of football and various scientific perspectives on the field - sociological, technical, tactical and performance. Purpose: This study aims to determine the relationship between anxiety levels and the risk of injury in amateur youth soccer players. Method: the research method used is quantitative observational with a cross sectional approach. A total of 80 amateur youth soccer players participated in this study, the parameters used were the Hamilton Rating Scale For Anxiety (HARS) to assess anxiety levels and functional movement screening to determine when an injury occurred and who had been injured. Results: It is known that from the 80 samples of this study, 66.3% of respondents had a mild level of anxiety and as many as 97.5% of respondents had a risk of sports injuries. Based on the results of data processing using SPSS 25.0 with normal distribution and the results of the bivariate test using the spearmen test, the results obtained between the Anxiety Level and the Risk of Occurrence of Sports Injuries have a sig value of 0.001, where p <0.05 results show that there is a relationship between the two variables, so that H1 is accepted. Conclusion: There is a significant relationship between the level of anxiety and the risk of sports injuries in amateur soccer players. Keywords: Anxiety; Relationship; The risk of injury